Alterations in Gut Microbial Communities Across Anatomical Locations in Inflammatory Bowel Diseases - Zhou, Youlian; He, Yan; Liu, Le; Zhou, Wanyan; Wang, Pu; Hu, Han; Nie, Yuqiang; Chen, Ye (Frontiers in Nutrition, 2021)
We previously discovered that gut microbiota can serve as universal microbial biomarkers for diagnosis, disease activity assessment, and predicting the response to infliximab treatment for inflammatory bowel diseases (IBD). Much still remains unknown about the relationship between alterations in gut microbiota and IBD affected bowel region, in particular in the case of ulcerative colitis (UC) and colonic Crohn’s disease (cCD) without endoscopic and biopsy data. In the current study gut microbiota from a population in China was found to be distinct from that of the Western world [Human Microbiome Project (HMP) data]. Furthermore, both gut microbiota greatly differed from microbiota of other anatomical locations (oral, skin, airway, and vagina), with higher alpha-diversity (Chinese gut > HMP gut > oral microbiome > airway microbiome > skin microbiome > vaginal microbiome), and marked differences in microbiome composition. In patients with IBD in China, UC was characterized by the presence of Gardnerella, while cCD was characterized by the presence of Fusobacterium. Moreover, gut microbiota, such as Gardnerella and Fusobacterium, may be potential biomarkers for identifying UC from cCD. Together, this study revealed crucial differences in microbial communities across anatomical locations, and demonstrated that there was an important association between IBD affected bowel region and gut microbiota.